2005
DOI: 10.1261/rna.2220705
|View full text |Cite
|
Sign up to set email alerts
|

Prp8 protein: At the heart of the spliceosome

Abstract: Pre-messenger RNA (pre-mRNA) splicing is a central step in gene expression. Lying between transcription and protein synthesis, pre-mRNA splicing removes sequences (introns) that would otherwise disrupt the coding potential of intron-containing transcripts. This process takes place in the nucleus, catalyzed by a large RNA-protein complex called the spliceosome. Prp8p, one of the largest and most highly conserved of nuclear proteins, occupies a central position in the catalytic core of the spliceosome, and has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
394
1
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(417 citation statements)
references
References 207 publications
(306 reference statements)
13
394
1
9
Order By: Relevance
“…It is the only spliceosomal protein that extensively cross-links with the 5Ј ss, BPS, 3Ј ss, U5, and U6, all key components of the splicing reaction (6). A large number of mutations in PRP8 were identified that suppress the U4-cs1 cold-sensitive mutant, illustrating the role of Prp8 in the spliceosome activation mediated by U4/U6 unwinding (7)(8)(9).…”
mentioning
confidence: 99%
“…It is the only spliceosomal protein that extensively cross-links with the 5Ј ss, BPS, 3Ј ss, U5, and U6, all key components of the splicing reaction (6). A large number of mutations in PRP8 were identified that suppress the U4-cs1 cold-sensitive mutant, illustrating the role of Prp8 in the spliceosome activation mediated by U4/U6 unwinding (7)(8)(9).…”
mentioning
confidence: 99%
“…Prp8 is the largest and most highly conserved spliceosomal protein 80 and forms a scaffold, on which the catalytic core of the spliceosome is assembled. 39,81 At its C-terminus, Prp8 comprises an RNase H-like (RH) domain [82][83][84] followed by a Jab1 domain, 85,86 both of which can regulate Brr2 function.…”
Section: Brr2 Regulation Via Trans-acting Factorsmentioning
confidence: 99%
“…Crosslinking experiments have indicated the proximity of Prp8 to both the 5' and 3' splice sites and the branch site, in addition to U6 and U5 snRNAs. 76,77 Thus, it is clear that Prp8 is closely associated with reacting groups in assembled spliceosomes. Further, mutations in Prp8 are known to affect the efficiency of either the first or second step of splicing, especially for suboptimal substrates.…”
Section: Catalytic Activity Of the Rna Elements Of The Active Site Inmentioning
confidence: 99%
“…Further, mutations in Prp8 are known to affect the efficiency of either the first or second step of splicing, especially for suboptimal substrates. 57,76,[78][79][80] This observation is best explained by a hypothesis stating that Prp8 is involved in stabilization of alternative, mutually-exclusive active site conformations that are either poised for catalysis of the branching reaction observed in the spliceosome, the cleavage of the 5' splice site occurs through hydrolysis in this minimal, RNA-only system. This could be due to the absence of a branch site-like substrate, which precludes a branching reaction.…”
Section: Catalytic Activity Of the Rna Elements Of The Active Site Inmentioning
confidence: 99%